Genetic predisposition to the presence and 5-year clinical progression of hip osteoarthritis. - Pollard, T; Batra, R; Judge, A; Watkins, B; McNally, E; Gill, H; Arden, N; Carr, A (2012)
Genetic factors are important in the aetiology of hip osteoarthritis (OA), but studies are limited by cross-sectional design and poor association with clinically important disease. Identifying cohorts with progressive OA will facilitate development of OA biomarkers. Using a middle-aged cohort with genetic predisposition to hip OA and a control group, we compared the prevalence of clinical and radiographic hip OA and incidence of progression over 5 years.